CREATING NEW STRATEGY FOR BUSINESS SUSTAINABILITY THROUGH BUSINESS MODEL CANVAS ( BMC ) EVALUATION IN PAPER MANUFACTURING - Eric Harianto; Eny Soenardi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
In addition to increasingly fierce global competition, the company is also faced with existing products that have entered the declining phase, newsprint and HVS Recycled paper so that the company must create new branding, new marketing for packaging paper and implement new strategies so that the company's revenue does not decline, but can be improved, both in terms of revenue and profit, and reduce operating costs. The analysis is carried out on each element of the Business Model Canvas, namely Customer Segments, Channels, Customer Relationships, Value Propositions, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. In the manufacturing industry, the hardest challenge is at the back stage, where companies are required to operate excellence in order to achieve cost efficiency and increase company profits. This research was conducted for six months starting from Januari 2021 to June 2021. In this study, the informant were 5 employees, consisting of 1 General Manager and 4 managers (production manager, purchasing manager, marketing manager and QC manager ). The data analysis technique used is descriptive analysis (Creswell,2014). Data testing in this study was carried out using the data triangulation method. This research was conducted at PT. Adiprima Suraprinta which is engaged in paper manufacturing with the aim of creating new strategies that are useful for business sustainability through Business Model Canvas (BMC) evaluation can be applied immediately. Keywords: Sustainibility, BMC, Strategy, Paper Manufacturing.